Terapi Doa dan Herbal Menggunakan Tumbuhan Pandan Berduri (Pandanus tectorius) dalam Mengobati Sakit Gigi - Mahdiya, Najma Nuro; Abdullah, Zuhair (Journal of Sufism and Psychotherapy, 2023)
The practice of treating toothache using prayer and herbs is still used by some people. Therefore, the purpose of the research namely: 1) to find out the practice of prayer and herbal therapy in treating toothache; 2) to know the benefits of prayer and herbal therapy. This research is a qualitative research, with the type of field research. The primary data sources in the study came from therapists and patients, while the secondary data sources came from books, scientific articles, websites and other relevant sources. Data collection techniques were carried out by interviews, observation, and documentation. The results of this study are: 1). therapy is carried out in several stages, first, the therapist reads prayers and short letters in the Koran; second, the therapist takes the sap of the Pandanus tectorius plant and attaches it to the outer area of the cheek which is close to the part of the tooth that hurts; third, the therapist ends the treatment by reading hamdalah. 2). according to the narrative of the patient, this therapy is beneficial to his recovery. Through the prayer given, the patient feels calm and peace of mind. Psychological conditions like this can bring out the hormone of happiness which also acts as a pain reliever. Scientifically, the Pandanus tectorius plant contains natural chemicals that are anti-inflammatory to reduce inflammation, analgesics to relieve pain, and antibiotics to kill germs and prevent infection. The benefits of prayer and natural chemicals are indicated to be intermediaries in the patient's recovery.